Original paperTransforming growth factor-β1 in plaque morphea - Dańczak-Pazdrowska, Aleksandra; Kowalczyk, Michał J.; Szramka-Pawlak, Beata; Gornowicz-Porowska, Justyna; Szewczyk, Aleksandra; Silny, Wojciech; Molińska-Glura, Marta; Olewicz-Gawlik, Anna; Żaba, Ryszard; Pazdrowski, Jakub; Hrycaj, Paweł (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: Morphea (localized scleroderma) is a rare cutaneous disease characterized by skin fibrosis of unknown pathogenesis. Transforming growth factor-β (TGF-β) is a potent profibrotic factor. The role of TGF-β in morphea remains unclear. Aim: The goal of this study was to estimate the expression level of TGF-β1 in skin and peripheral blood mononuclear cells as well as the plasma levels of TGF-β1 in plaque morphea (MEP). Material and methods: The study involved 20 MEP patients. Three control groups were involved: 1 – plasma: 36 healthy volunteers; 2 – PBMC: 47 healthy volunteers; 3 – skin biopsies: 13 samples collected during mastectomy (breast cancer was not skin involved). The analysis of TGF-β1 plasma levels was performed with the use an adequate ELISA kit, while real-time polymerase chain reaction was employed for the expression of TGF-β1 in peripheral blood mononuclear cells (PBMC) and skin. Results: In our study we have not detected differences in TGF-β 1 expression in PBMC, skin, nor in plasma levels of TGF-β1 between MEP patients and healthy controls, regardless of disease activity and its duration. Conclusions: : The results of our study contradict the claim of the substantial role of TGF-β1 in the most common morphea subtype – MEP.